Frog Skin Derived Peptides With Potential Protective Effects on Ultraviolet B–Induced Cutaneous Photodamage - Liu, Han; Guo, Xiaopu; Yi, Tangwei; Zhu, Yihan; Ren, Xinyi; Guo, Renxian; Dai, Yi; Liang, Shaohui (Frontiers in Immunology, 2021)
Hyla annectans is a tree frog living in the subtropical plateau where there is strong ultraviolet radiation and long duration of sunshine. So their naked skin may possess chemical defense components which protect it from acute photo-damage. However, no such peptide or components has been identified till to date. In the current work, two novel peptides (FW-1, FWPLI-NH2 and FW-2, FWPMI-NH2) were identified from the skin of the tree frog. Five copies of FW-1 and four copies of FW-2 are encoded by an identical gene and released from the same protein precursor which possess 167 amino acid residues. FW-1 and -2 can exert significant anti-inflammatory functions by directly inhibiting UV-induced secretion of inflammatory cytokines such as tumor necrosis factor- and interleukin-6 both in vitro and in vivo. They may achieve this function by modulating the UV-induced stress signaling pathways such as MAPK and NF-B. Besides, FW-1 and -2 showed a potential antioxidant effects on epidermis by attenuating the UVB-induced ROS production through an unknown mechanism. Considering their easy production, storage, transfer and potential photo-protective activity, FW-1/2 might be exciting leading compounds or templates for the development of novel pharmacological agents for the suppression of UV-induced skin inflammation and potentially tumorigenesis. In addition, this study might facilitate to understand skin defensive mechanism of amphibians upon UV irradiation.